Catch that cookie! - Durand, Hallie (Dial Books for Young Readers, an imprint of Penguin Group (USA) Inc., 2014)
Marshall refuses to believe that gingerbread men can run, even after a series of clues leads his class on a riddle-filled gingerbread cookie hunt.